2018
DOI: 10.1016/j.phrs.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Helminth infection in mice improves insulin sensitivity via modulation of gut microbiota and fatty acid metabolism

Abstract: Intestinal helminths are prevalent in individuals who live in rural areas of developing countries, where obesity, type 2 diabetes, and metabolic syndrome are rare. In the present study, we analyzed the modulation of the gut microbiota in mice infected with the helminth Strongyloides venezuelensis, and fed either a standard rodent chow diet or high-fat diet (HFD). To investigate the effects of the microbiota modulation on the metabolism, we analyzed the expression of tight-junction proteins present in the gut e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 88 publications
4
43
1
Order By: Relevance
“…Recent findings suggest that moderate gut dysbiosis exists in DM patients and animal models . Although the characteristics of the DM gut microbiome are still mired in controversy, gut microbiome studies have hinted at the biological functions or pathogenic roles of gut microbiota in DM progression . The differential richness of specific bacteria is potentially correlated with DM development .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings suggest that moderate gut dysbiosis exists in DM patients and animal models . Although the characteristics of the DM gut microbiome are still mired in controversy, gut microbiome studies have hinted at the biological functions or pathogenic roles of gut microbiota in DM progression . The differential richness of specific bacteria is potentially correlated with DM development .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Although the characteristics of the DM gut microbiome are still mired in controversy, gut microbiome studies have hinted at the biological functions or pathogenic roles of gut microbiota in DM progression. [14][15][16] The differential richness of specific bacteria is potentially correlated with DM development. 17 Faecalibacterium prausnitzii (F. prausnitzii) are the predominant butyrateproducing bacteria in the gastrointestinal tract.…”
mentioning
confidence: 99%
“…Among the varieties of analytical platforms used for metabonomic analysis, the use of ultra performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS) is steadily increasing due to its better reproducibility and detection limits, and increased chromatographic resolution, which can assess all metabolites in biological samples and provide insights into the holistic efficacy of TCMs. Besides, the extent of metabolic changes and types of metabolites could be applied as good markers during insulin resistance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…H. polygyrus, N. brasiliensis and T. muris infections were all shown to induce an increase in Lactobacillaceae, and members of this family are widely recognised as having probiotic potential by virtue of their ability to regulate immune responsiveness . Recently, a study investigating Strongyloides venezuelensis and DIO showed an improvement of insulin sensitivity upon infection, and these benefits were linked to a modification of microbiota, including an increase in several species of Lactobacillus, and a reduction of intestinal permeability (Figure ) . As mentioned earlier, one recent study reported that the beneficial effects of H. polygyru s infection on DIO in mice were positively associated with a modification of the microbiota leading to an increased level of circulating NE .…”
Section: Helminth Infection and Metabolic Statusmentioning
confidence: 63%
“…76,87,88 Recently, a study investigating Strongyloides venezuelensis and DIO showed an improvement of insulin sensitivity upon infection, and these benefits were linked to a modification of microbiota, including an increase in several species of Lactobacillus, and a reduction of intestinal permeability (Figure 2). 89 As mentioned earlier, one recent study reported that the beneficial effects of H. polygyrus infection on DIO in mice were positively associated with a modification of the microbiota leading to an increased level of circulating NE. 70 As also mentioned earlier, adapting to stress, such a helminth infection, requires proper energetic balance and helminths are able to alter glucose uptake within the intestine, 62 likely resulting in restricted caloric intake.…”
Section: Possible Contribution Of Helminthmicrobiota Interactions On mentioning
confidence: 81%